1991
DOI: 10.1093/cvr/25.8.622
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic calcium staircase in ventricular myocytes isolated from guinea pigs and rats

Abstract: Tension staircase of mammalian hearts depends on diastolic Ca2+ level as well as Ca2+ handling by the sarcoplasmic reticulum. The positive staircase may require progressive increase in diastolic [Ca2+]i, while the negative staircase may be mediated by depletion of activator Ca2+ in the sarcoplasmic reticulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…This concealed positive FFR is 21 of the animals in this study demonstrated this late phase. not associated with increased SR Ca release upon higher Thus, analogous to isolated papillary muscle, the results of rates of stimulation [26], but is correlated with increased 21 this study are consistent with ryanodine induced transintracellular Ca levels. Thus, akin to MR, FFR amplifi- 21 21 formation of myocardial Ca handling from being precation is consistent with increased importance of SL Ca dominantly SR dependent to predominantly SL dependent.…”
Section: Essupporting
confidence: 76%
“…This concealed positive FFR is 21 of the animals in this study demonstrated this late phase. not associated with increased SR Ca release upon higher Thus, analogous to isolated papillary muscle, the results of rates of stimulation [26], but is correlated with increased 21 this study are consistent with ryanodine induced transintracellular Ca levels. Thus, akin to MR, FFR amplifi- 21 21 formation of myocardial Ca handling from being precation is consistent with increased importance of SL Ca dominantly SR dependent to predominantly SL dependent.…”
Section: Essupporting
confidence: 76%
“…The authors suggested that this increase in diastolic Ca 2ϩ contributed to positive inotropic effects by increasing SR stores (19). Interestingly, Hattori et al (20) showed that increases in diastolic Ca 2ϩ might play a direct role in mediating positive staircases, which were generated by stimulating cardiac myocytes following a period of rest. In this study, positive staircases were directly related to progressive increases in diastolic [Ca 2ϩ ] and were preserved when SR Ca 2ϩ release was blocked by ryanodine (20).…”
mentioning
confidence: 99%
“…Interestingly, Hattori et al (20) showed that increases in diastolic Ca 2ϩ might play a direct role in mediating positive staircases, which were generated by stimulating cardiac myocytes following a period of rest. In this study, positive staircases were directly related to progressive increases in diastolic [Ca 2ϩ ] and were preserved when SR Ca 2ϩ release was blocked by ryanodine (20). Ryanodine should remove the contribution of SR Ca 2ϩ release to staircases, and therefore this observation suggests a role for changes in diastolic Ca 2ϩ in generation of staircases (20).…”
mentioning
confidence: 99%
“…This suggests that an increase of intracellular calcium level is associated with ricin's toxicity. Based on studies of single myocardial cells, a cumulative increase in resting ICa2+], can result from Ca2+ handling by the sarcoplasmic reticulum (21). The mechanism for this rise in [Ca2+], can be secondary to decreased calcium uptake by the sarcoplasmic reticula (22) or through increased Na+-Ca2+ exchange (23).…”
Section: Discussionmentioning
confidence: 99%